Seroprevalence of antibodies to measles, mumps, and rubella, and serologic responses after vaccination among human immunodeficiency virus (HIV)-1 infected adults in northern thailand - Romanee Chaiwarith (2018)
© 2016 Chaiwarith et al. Background: After the global implementation of national immunization programs for prevention of measles, mumps, and rubella (MMR), the prevalences of protective antibodies to these viruses are high in general population. However, there are limited data among human immunodeficiency virus (HIV)-1 infected individuals. This study aimed to determine the seroprevalence of antibodies to these viruses, and the serologic responses after vaccination among HIV-infected adults in Northern Thailand. Methods: A cross-sectional study was conducted in 500 HIV-infected adults, aged 20-59 years, receiving combination antiretroviral therapy, CD4 cell count ≥200 cells/mm3, and plasma HIV-1 RNA <50 copies/mL, and 132 HIV-uninfected controls, aged 20-59 years, at Chiang Mai University Hospital during July and August 2011. Prevalences of protective antibodies to these viruses as well as serologic responses after MMR vaccination in those without protective antibody to at least one of the three viruses were compared between groups. Results: The prevalences of protective antibodies to measles, mumps, and rubella were 94.2, 55.0, and 84.6 % among HIV-infected adults, and 97.7, 67.5, and 89.4 % among HIV-uninfected controls, respectively. The prevalence of protective antibody to mumps was significantly lower in HIV-infected adults (p-value = 0.010). MMR vaccination was done in 249 HIV-infected and 46 HIV-uninfected controls; at week 8 to 12 after vaccination, the seroprotective rates against measles, mumps, and rubella in HIV-infected adults were 96.4, 70.7, and 98.0 %, respectively, whereas those in HIV-uninfected controls were 100, 87, and 100 %, respectively. No serious adverse effects were observed. Conclusions: In contrast to measles and rubella, the prevalence of protective antibody to mumps was low in both HIV-infected adults and HIV-uninfected controls in northern Thailand. The seroprotective rates after MMR vaccination in both groups were considerably high, except only for mumps. Therefore, MMR vaccination should be considered in all HIV-infected adults receiving antiretroviral therapy with undetectable plasma HIV-1 RNA and CD4 cell count ≥200 cells/ mm3. Trial registration: ClinicalTrials.gov: NCT02724852, registered on March 31, 2016.